Thermal, photoresponsive and conductivity studies of nitroazobenzene polymer: article - Mohamad Iskandar, Nur Afiqah; Mohd Alauddin, Sakinah (2019)
The thermal properties, photoresponsive and conductivity studies of nitroazobenzene polymers of both homopolymer and terpolymer are studied. The poly[6-(4-nitro4-oxyazobenzene) hexylmethacrylate] (AzoN6) homopolymer and terpolymer consisting of sulfonic acid (AMPS) and methyl methacrylate (MMA) were synthesized by radical polymerization. Both of the samples were characterized by Differential Scaning Calorimetry (DSC), thermogravimetric analysis (TGA), UV-Visible spectrophotometry and electrochemical impedance spectroscopy (EIS). The azobenzene group that attached with –NO₂ in the polymers revealed that the homopolymer and terpolymer have light responsive properties and exhibit glass transition at considerably low temperature. Detailed conductivity showed that the ionic conductivity for both polymers is in the range of 10-⁹ -10-⁷ S.cm-¹ and increasing with increase temperature.